Построение геоэлектрических 3D моделей металлогенических и очаговых зон Алтае-Саянского региона - Белявский, В.В. (Наукові праці УкрНДМІ НАН України, 2013)
Показано, що 3D інверсія магнітотелуричних даних дозволяє побудувати геоелектричні моделі осередкових і металогенічних зон, оцінити їхній зв'язок з сейсмічністю і мінерагенією регіону. It is shown, that 3D inversions МТZ data allows to construct geoelectric models of the centers of earthquakes and metals zones to estimate the maintenance of a fluid in domains and their communication with seismicity and minerals region.